Depth image-based spatial error concealment for 3-D video transmission - Ali, ‘Abidah; Abdul Karim, Hezerul; Mohd Arif, Nor Azhar; Sali, Aduwati (IEEE, 2010)
An alternative form of stereoscopic video is the combination of 2-D video from an ordinary 2-D video camera and depth information from a laser range or depth camera. When this type of 3-D video is compressed and transmitted over error prone channels, the associated packet loss leads to poor visual quality. Therefore, a depth image-based error concealment for 3-D video transmission is proposed, which utilizes a strong correlations between 2-D video and its corresponding depth map. The depth information provides an indication of object boundaries to assist the concealment process. This spatial object based error concealment involves concealment decision process and frequency extrapolation.